Hubungan Pengetahuan dan Sikap Ibu dengan Pemijatan Bayi di Wilayah Kerja Puskesmas Selagan Raya Kabupaten Mukomuko - Nova Jalaria; Tita Septi Handayani; Ronalen Br. Situmorang (Utami Publisher, 2026)
Infancy is a golden period for child growth and development so it needs special attention. One factor that influences infant growth and development is adequate sleep and rest. Sleep needs are not only seen from the aspect of quantity but also its quality. With good quality sleep, infant growth and development can be achieved optimally (Widyanti, 2012 in Nurcahaya, 2020). The research method used is quantitative with a total sample of 146 mothers who have babies. The independent variables are mothers’ knowledge and attitudes and the dependent variable is infant massage. The data analysis of this study used the Chi Square statistical test (α = 0.05). The results of the author's study showed that more than half of the respondents, namely 92 (63.0%) respondents had sufficient knowledge of infant massage. Some respondents, namely 63 (43.0%) respondents had negative attitudes towards infant massage. More than half of the respondents, namely 60 (41.1%) respondents did not perform infant massage. The chi-square test results showed a relationship between maternal knowledge and attitudes and infant massage in the Working Area of Selagan Raya Health Center, Mukomuko Regency, with p = 0.000, meaning p < 0.05, meaning the HI was accepted. The conclusion of this study is that there is a correlation between mothers’ knowledge and attitudes and infant massage in the Working Area of Selagan Raya Health Center, Mukomuko Regency. Infant massage should be provided at health centers (BPM), health center, hospitals, and other health care facilities to improve the knowledge and attitudes of mothers with infants. Infant massage can also be provided by midwives or health workers who have received training in infant massage and are certified.